2017
DOI: 10.1063/1.4996047
|View full text |Cite
|
Sign up to set email alerts
|

The characters of ion acoustic rogue waves in nonextensive plasma

Abstract: Several well-known nonlinear waves in the rational solutions of the nonlinear Schrödinger equation are studied in two-component plasmas consisting of ions fluid and nonextensive electrons, such as Kuznetsov–Ma breather (K-M), bright soliton, rogue wave (RW), Akhmediev breather (AB) and dark soliton, and so on. In this paper, we have investigated the characteristics of K-M, AB, and RW's propagation in plasma with nonextensive electron distribution, and the dependence of amplitude and width for ion acoustic rogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…[48][49][50][51] It has indicated that the long-range interactions systems, gravitational systems, also in a lot of space plasmas, in addition laboratory plasmas, the edge of tokamak plasma (in which for the current drive, lower hybrid waves have been used), the Maxwellian velocity distribution (based on Boltzmann-Gibbs statistics) is not adequate for the explanation of the system. [52][53][54][55][56][57][58] Recently, the nonextensive statics or Tsallis statistics has been successfully applied to study the electrostatic solitary waves. [5,[59][60][61][62][63] The q-nonextensive distribution for hot plasma species, which presented nonthermality of plama, have the below distribution function.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50][51] It has indicated that the long-range interactions systems, gravitational systems, also in a lot of space plasmas, in addition laboratory plasmas, the edge of tokamak plasma (in which for the current drive, lower hybrid waves have been used), the Maxwellian velocity distribution (based on Boltzmann-Gibbs statistics) is not adequate for the explanation of the system. [52][53][54][55][56][57][58] Recently, the nonextensive statics or Tsallis statistics has been successfully applied to study the electrostatic solitary waves. [5,[59][60][61][62][63] The q-nonextensive distribution for hot plasma species, which presented nonthermality of plama, have the below distribution function.…”
Section: Introductionmentioning
confidence: 99%